Optimization of Somatic Embryogenesis Induction of Cassava (Manihot esculenta Crantz) - Susanti, Idha; Suharsono, Suharsono; Widyastuti, Utut; Siregar, Ulfah Juniarti; Tjahjoleksono, Aris (Annales Bogorienses, 2017)
The embryogenesis (SE) has important role for genetic engineering of cassava (Manihot esculenta Crantz). However, the success of SE induction depend on plant growth regulator s (PGR)s and treatment enriched in induction media. This experiment tried to induce callus formation of cassava from several in vitro explants: immature leaf, apical bud, and internode; and to develop somatic embryogenesis of cassava in several media enriched with tyrosine and copper sulphate (CuSO4) added into media enrich with picloram as treatment. Different response of explants source to callus induction treatment from those three varieties in callus induction as well as friable callus formation were found in this experiment. The best medium to induce varied with variety; MS media supplemented 12 mg/L picloram + 0.5 mg/L CuSO4 was the best for “Adira 4” and half MS and half GD media supplemented 12 mg/L picloram + 100 mg/L tyrosine for “Malang 6”. All treatments resulted somatic embryo which developed indirectly and in morphologically normal somatic embryos